PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, KOMPENSASI EKSEKUTIF DAN KEPEMILIKAN MANAJERIAL TERHADAP TAX AVOIDANCE - Sasriani, Nur Alfiah; Sugeng, Andry (Jurnal Nusa Akuntansi, 2025)
This research aims to determine and obtain empirical evidence of the influence of Corporate Social Responsibility Disclosure, Executive Compensation, and Managerial Ownership on Tax Avoidance in Consumer Non Cyclical companies listed on the BEI in 2018 - 2022. The dependent variable in this research is Tax Avoidance, while the Variable independent in this research, namely Disclosure of Corporate Social Responsibility, Executive Compensation, and Managerial Ownership. This research is quantitative and uses associative methods and data sourced from company annual reports for the 2018 - 2022 period with panel data regression analysis techniques. The research results show that the Corporate Social Responsibility Disclosure variable has no significant effect on Tax Avoidance in Consumer Non Cyclical companies listed on the Indonesia Stock Exchange for the 2018-2022 period, Executive Compensation has no significant effect on Tax Avoidance in Consumer Non Cyclical companies listed on the Stock Exchange Indonesia for the 2018-2022 period, Managerial Ownership has no significant effect on Tax Avoidance in Consumer Non Cyclical companies listed on the Indonesia Stock Exchange for the 2018-2022 period and Disclosure of Corporate Social Responsibility, Executive Compensation and Managerial Ownership simultaneously have a significant effect on Tax Avoidance in companies Consumer Non Cyclicals listed on the Indonesia Stock Exchange for the 2018-2022 period.